Consistency - Kiki Rahmatika (Graduate School of Institut Seni Indonesia Yogyakarta, 2017)
This choreography is started from Practice based Research. The research is about Dajang Rindoe’s manuscript which is deconstructed. In the process of cultivation of this work, the foundation of creation used text deconstruction, creativity, and choreography. Text deconstruction is implemented in finding the new point of view of the women freedom. Creativity approach is used for the reason that the artwork creation is not separated from the thinking process and work creatively. By this approach, the way of thinking and working creatively will be developed. The third approach that is choreography is used as the foundation in creating the dance aesthetic that involving the body movement, composition, unity, harmony, behaviour and other visual aspects. CONSISTENCY dance work is a description about woman toughness to get her freedom in order to maintain her integrity. The freedom that need the full struggle for her to get. Because the freedom itself has the meaning to be able to live independently and responsibly. In the real life, the freedom women who able to preserve her firmness independently and responsibly are very scarce. The imbalance of this firmness then fades the women integrity.